Pengaruh Celebrity Endorsement, Kualitas Produk Dan Daya Tarik Iklan Di Media You Tube Terhadap Minat Beli (Studi Pada FEB Angkatan 2017 Unisma) - Subur Widiyanto; Nur Hidayati; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine and analyze the effect of celebrity endorsemet, product quality, and the attractiveness of advertisements on You Tube media on the buying interest of FEB Unisma Malang students. This research is a type of explanatory research, with a quantitative approach. The analytical method used is multiple linear regression analysis. The sample used in this study using the Maholtra formula with purposive sampling technique obtained 64 respondents.The results of this study indicate that partially there is a significant influence between celebrity endorsements on buying interest, product quality has a significant effect on buying interest, advertising attractiveness has a significant effect on buying interest in FEB Unisma Malang students.  Keywords: Celebrity Endorsemet, Product Quality, Advertising Attractiveness and Purchase Interest